Diagnosing and treating psoriatic arthritis: an update. (1st April 2014) - Boehncke, W.H.; Qureshi, A.; Merola, J.F.; Thaçi, D.; Krueger, G.G.; Walsh, J.; Kim, N.; Gottlieb, A.B.
Summary: Psoriatic arthritis (PsA) is an inflammatory arthritis of uncertain pathogenesis, affecting approximately one in four patients with psoriasis. Onset of psoriasis typically precedes the development of PsA. Therefore, the dermatologist is ideally positioned to recognize the early signs and symptoms of PsA for diagnosis and subsequent treatment. The role of the dermatologist in early diagnosis and treatment is essential for preventing pain and functional disabilities, as well as the joint deterioration that accompanies progressive forms of PsA. Diagnosis of PsA is a key aspect of the clinical decision process for the dermatologist, as psoriasis plus PsA requires a different therapeutic approach from that required for psoriasis alone. Furthermore, PsA is associated with an increased risk of cardiovascular comorbidities that present significant health concerns. In this review, the pathogenesis and comorbidities of PsA are discussed. In addition, screening and imaging tools that aid in the diagnosis of PsA, as well as tools used for efficacy assessment, are reviewed. Available therapies are presented, with a focus on targeted biologics and emerging treatments.